Three-stage model based evaluation of local residents' acceptance towards waste-to-energy incineration project under construction A Chinese perspective - Fu, Lingmei (Waste management (New York, N.Y.), 2021)
Copyright © 2020 Elsevier Ltd. All rights reserved.